2021
DOI: 10.1111/jtxs.12630
|View full text |Cite
|
Sign up to set email alerts
|

Influence of milling methods on the flow properties of ivory teff flour

Abstract: Increasing teff (Eragrostis tef) consumption has been recorded in recent years due to its gluten‐free nature and exceptional nutritional composition. Studies on the particle level that relates to processing and handling of teff flour are limited. The effect of different milling methods (roller mill, pin mill, and hammer mill) on size distribution, shape characteristics, and flowability of teff flour was evaluated. Physical properties (angle of repose, tapped and bulk densities, size distribution, and shape cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(67 reference statements)
2
5
0
Order By: Relevance
“…The GMD data provided in Table 3 also denote that pin mill flour fraction had the lowest average particle size of 75 μm as compared to flours obtained through other mill types. Similar trend was observed by Barretto, Buenavista, Pandiselvam, and Siliveru (2021) for the particle size analysis of ivory teff flours, that is, hammer milled flour had higher percentage of coarser particles and pin milled flours resulted in higher quantity of finer particles. The higher percentage of coarser particles in case of hammer mill is due to the use of 1/64 in.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The GMD data provided in Table 3 also denote that pin mill flour fraction had the lowest average particle size of 75 μm as compared to flours obtained through other mill types. Similar trend was observed by Barretto, Buenavista, Pandiselvam, and Siliveru (2021) for the particle size analysis of ivory teff flours, that is, hammer milled flour had higher percentage of coarser particles and pin milled flours resulted in higher quantity of finer particles. The higher percentage of coarser particles in case of hammer mill is due to the use of 1/64 in.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, we observed that the ash content for the teff flour obtained from hammer mill was significantly higher compared to other two mills. The proximate composition of all the three brown teff flours closely matches with the ivory teff flours obtained by different milling methods by Barretto, Buenavista, Pandiselvam, and Siliveru (2021). A significantly lower damaged starch content (2.61%) was observed in case of hammer‐milled teff flour compared to the roller‐ (6.16%) and pin‐milled (4.88%) flours.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Another study investigated the use of teff flour in bread, layer cakes, treats, and rolls and discovered that it is best used in treats and rolls (Barretto et al, 2021). In a study, Frakolaki et al (2020) exploited the properties (batter volume extension, particular volume, hull, and piece color, hardness, and water movement) and breadmaking potential of naturally heated and solidified pastry shop items amid halfway substitution of wheat flour with spelt flour and found that spelt flour extends up to 20% give bread with quality and tactile characteristics comparative to wheat, whereas it extends higher than 70% lead to second rate items.…”
Section: Current Scenari Os Of Whe At Alternative Smentioning
confidence: 99%
“…Water and oil holding capacities were determined using the modified method of Zhao et al (2010). The MOS was beneficial to increasing the particle-specific surface area and cell wall breakage ratio, thereby accelerating the dissolution of bioactive ingredients and improving bioavailability and bioactivity in vivo or in vitro (Xiao et al, 2017;Zhang & Zhai, 2020;Barretto et al, 2021;Balakrishnan et al, 2021;Qadri et al, 2022). Huang et al (2020) found that the decrease in particle size significantly reduced the water and oil holding capacities while increasing the lightness and yellowness of M. oleifera leaf powders.…”
Section: Water and Oil Holding Capacitiesmentioning
confidence: 99%